Stability and Boundedness of Stochastic Volterra Integrodifferential Equations with Infinite Delay - Chunmei Zhang; Wenxue Li; Ke Wang (Journal of Applied Mathematics)
We make the first attempt to discuss stability and boundedness of solutions to stochastic Volterra integrodifferential equations with infinite delay (IDSVIDEs). By the Lyapunov-Krasovskii functional approach, we get kinds of sufficient criteria for stability and boundedness of solutions to IDSVIDEs. The main innovation here is that stochastic systems with infinite delay can retain stability and boundedness of corresponding deterministic systems under some conditions.